Comparison of del Nido Cardioplegia With Blood Cardioplegia in Adult Combined Surgery. Issue 5 (September 2017) - Hamad, Raphael; Nguyen, Anthony; Laliberté, Éric; Bouchard, Denis; Lamarche, Yoan; El-Hamamsy, Ismail; Demers, Philippe
Abstract : Objective: del Nido solution (DNS) is a single-dose cardioplegia designed for pediatric use proposed to offer superior myocardial protection in adults. However, few data support this claim. We hypothesized that DNS and modified blood cardioplegia solution (BS) provide equivalent safety in combined adult valve surgery. Methods: Between November 2014 and December 2015, 25 patients underwent primary aortic valve replacement and concomitant coronary artery bypass grafting (CABG) with DNS. Outcomes were compared with 25 patients who underwent the same surgery with BS between September 2013 and August 2015. Results: All preoperative characteristics, comorbidities, and number of CABG performed were similar between groups. One hospital death occurred in the BS group. Postoperative creatine kinase, MB isotype (16.7 ± 5.3 μg/L vs. 22.1 ± 8.9 μg/L, P = 0.011) and troponin T levels (260 ± 105.3 ng/L vs. 370.5 ± 218.4 ng/L, P = 0.028) were significantly lower in the DNS group. There was no difference in inotropic or vasoactive agent use ( P = 0.512). Cardiopulmonary bypass times (65.5 ± 12.5 min vs. 76.6 ± 19.1 min, P = 0.019) and cross-clamp times (55.6 ± 11.2 min vs. 64.3 ± 18.9 min, P = 0.05) were lower in the DNS group but total operating room times ( P = 0.198) were similar. Peak postoperative creatinine levels were similar in both groups ( P = 0.063). There was no difference in postoperative outcomes including acute renal failure ( P > 0.999), atrial fibrillation ( P = 0.773), acute respiratory failure ( P > 0.999), nor stroke or transient ischemic attack ( P > 0.999). Intensive care unit stay ( P = 0.213) and hospital stay ( P = 0.1) did not differ between groups. Conclusions: The DNS can be used as an alternative to BS in adult concomitant aortic valve replacement + CABG surgery. This supports our hypothesis that in this specific setting, DNS provides comparable myocardial protection as BS, with possibly shorter cardiopulmonary bypass and cross-clamp times.